An additional study of multi-muon events produced in pp- collisions at s=1.96 TeV - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; Ashmanskas, W; et al. (2012)
We present one additional study of multi-muon events produced at the Fermilab Tevatron collider and recorded by the CDF II detector. We use a data set acquired with a dedicated dimuon trigger and corresponding to an integrated luminosity of 3.9 fb -1. We investigate the distribution of the azimuthal angle between the two trigger muons in events containing at least four additional muon candidates to test the compatibility of these events with originating from known QCD processes. We find that this distribution is markedly different from what is expected from such QCD processes and this observation strongly disfavors the possibility that multi-muon events result from an underestimate of the rate of misidentified muons in ordinary QCD events. © 2012 Elsevier B.V.